Production of rhamnose from pomelo peel using locally-isolated fungi Trametes sp. IP3 - Salihan, Nur Haziqah Aniyah (2016)
Pomelo fruit (limau bali) is very popular due to its huge flesh compared to the typical citrus fruit, orange. Malaysia produce in average around 8 000 tons of pomelo each year. However, because pomelo has a very thick skin, it was not highly demand by the industry. Despite its think skin (peel), the peel contains a rich source of flavonoid; naringin. Naringin, a bitter taste of flavonoid can be biodegraded into rhamnose and glucose with the presence of naringinase enzyme; β-glucosidase and α-L-rhamnosidase. Rhamnose is a typical 6-deoxyhexose similar to fucose and exhibits a taste similar to D-mannose and usually found in plant as a constituent of glycosides such as naringin. Many researches use chemical hydrolysis to obtain rhamnose from naringin. Rhamnose can be used to produce food flavour such as 4-hydroxy-2,5-dimethyl-furanone (HDMF) that was used abundantly in food flavor production for example Nestle as caramel flavour. Due to the abundance of acid used for the production of the food flavor, the process is not suitable for environmental friendly food production. As an alternative, rhamnose was obtained through microbial hydrolysis using enzyme from fungi. Therefore, this study was done to produce rhamnose and glucose using microbial (isolated fungi) process using the pomelo waste product (peel) as the main substrate with the minimal usage of harzardous chemical. In this study, 84 strains were isolated and it was found that strain IP 3 was able to produce 18.15 g/L rhamnose from 100 g/L dry treated pomelo peel, and 8.96 g/L of rhamnose from untreated pomelo peel. Trametes sp. IP3 has the potential to produce high naringinase enzyme for the bioconversion of naringin into rhamnose. However, the production of glucose was not reported with the production of rhamnose. Thus, a hydrolysate containing high activity (53.4 U/mL) of β-glucosidase enzyme from fermentation of Ganoderma lucidum (compost OPEFB as the substrate) was added to the fermentation media at day 6. Additional sugars were detected at the end of experiment; xylose, mannose, and rhamnose however, glucose was not detected. Nevertheless, Trametes sp. IP3 possesses the ability to produce sugars besides rhamnose with the presence of high activity of β-glucosidase enzyme.